The Influence of Tax Planning and Firm Size on Profitability in Indonesian Food and Beverage Manufacturers - Darwati; Rezky Ramadhani (www.amertainstitute.com, 2026)
Profitability is an important aspect for companies in improving performance and maintaining business continuity. This research aims to determine the effect of tax planning and company size on profitability in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2023–2025 period. This research uses quantitative methods with an associative causality approach and uses secondary data in the form of company annual financial reports. The sampling technique uses a purposive sampling method to obtain a sample of companies that meet the research criteria. Data analysis was carried out using multiple linear regression to determine the influence of the independent variable on the dependent variable partially or simultaneously. The results of the research show that tax planning and company size have different relationship directions on profitability, but partially both do not have a significant effect on company profitability. The research results also show that the ability of the two variables to explain profitability is still relatively low so that there are other factors outside the research model that more dominantly influence company profitability.